Cyclo‐P4 Building Blocks: Achieving Non‐Classical Fullerene Topology and Beyond. Issue 47 (26th October 2016) - Dielmann, Fabian; Peresypkina, Eugenia V.; Krämer, Barbara; Hastreiter, Florian; Johnson, Brian P.; Zabel, Manfred; Heindl, Claudia; Scheer, Manfred
Abstract: The cyclo‐P4 complexes [Cp R Ta(CO)2 (η 4 ‐P4 )] (Cp R : Cp′′=1, 3‐C5 H3 tBu2, Cp′′′=1, 2, 4‐C5 H2 tBu3 ) turned out to be predestined for the formation of hollow spherical supramolecules with non‐classical fullerene‐like topology. The resulting assemblies constructed with CuX (X=Cl, Br) showed a highly symmetric 32‐vertex core of solely four‐ and six‐membered rings. In some supramolecules, the inner cavity was occupied by an additional CuX unit. On the other hand, using CuI, two different supramolecules with either peanut‐ or pear‐like shapes and outer diameters in the range of 2–2.5 nm were isolated. Furthermore, the spherical supramolecules containing Cp′′′ ligands at tantalum are soluble in CH2 Cl2 . NMR spectroscopic investigations in solution revealed the formation of isomeric supramolecules owing to the steric hindrance caused by the third tBu group on the Cp′′′ ligand. In addition, a 2D coordination polymer was obtained and structurally characterized. Abstract : The self‐assembly of cyclo ‐P4 complexes [Cp R Ta(CO)2 (η 4 ‐P4 )] (Cp R =Cp′′, Cp′′′) and CuX results in spherical supramolecules with non‐classical fullerene‐like topology (X=Cl, Br) and two supramolecules with unprecedented peanut‐ and pear‐like scaffolds (X=I). The outer diameter of the macromolecules reached 2.5 nm. The solubility of the Cp′′′ derivatives enabled their NMR spectroscopic characterization in solution.